Fungal strain and crop cultivar affect growth of sweet pepper plants after root inoculation with entomopathogenic fungi - Wilberts, Liesbet; Rojas-Preciado, Nicolas; Jacquemyn, Hans; Lievens, Bart (Frontiers in Plant Science, 2023)
As endophytes, entomopathogenic fungi can protect plants against biotic and abiotic stresses and at the same time promote plant growth and plant health. To date, most studies have investigated whether Beauveria bassiana can enhance plant growth and plant health, while only little is known about other entomopathogenic fungi. In this study, we evaluated whether root inoculation of the entomopathogenic fungi Akanthomyces muscarius ARSEF 5128, B. bassiana ARSEF 3097 and Cordyceps fumosorosea ARSEF 3682 can promote plant growth of sweet pepper (Capsicum annuum L.), and whether effects are cultivar-dependent. Plant height, stem diameter, number of leaves, canopy area, and plant weight were assessed four weeks following inoculation in two independent experiments using two cultivars of sweet pepper (cv. ‘IDS RZ F1’ and cv. ‘Maduro’). Results showed that the three entomopathogenic fungi were able to enhance plant growth, particularly canopy area and plant weight. Further, results showed that effects significantly depended on cultivar and fungal strain, with the strongest fungal effects obtained for cv. ‘IDS RZ F1’, especially when inoculated with C. fumosorosea. We conclude that inoculation of sweet pepper roots with entomopathogenic fungi can stimulate plant growth, but effects depend on fungal strain and crop cultivar.